Rising Powers and Peacebuilding Breaking the Mold? - Call, Charles T.; de Coning, Cedric (Rethinking Peace and Conflict Studies,, 2017)
This book is open access under a CC BY 4.0 license. "This important book, recommended for practitioners and scholars alike, demonstrates that the future of peacebuilding will be unlike its past. The discrediting of traditional policy practices matched by the increasing role of rising powers means that peacebuilding approaches are rapidly changing. This collection makes a vital contribution, and poses a set of new and pressing questions." David Chandler, University of Westminster, author of Peacebuilding: The Twenty Years' Crisis, 1997-2017 "This excellent collection reflects on the changing nature of peacebuilding and offers an insightful examination of the growing role of rising powers in peacebuilding. It is a major contribution to the study of rising powers in general and peacebuilding in particular." Emel Parlar Dal, Marmara University, Turkey, and Editor of Rising Powers Quarterly "As former Chairman of the Peacebuilding Commission, I have sought to express Brazil's commitment to effectively contribute to end conflict and improve conditions for sustainable development and peace. Two notions have established themselves as essential: multilateralism and diplomacy. The points raised by this book help to illustrate the importance of the United Nations and the primacy of politics and diplomacy in advancing the cause of sustaining peace." Antonio Patriota, Ambassador to Rome, former Permanent Representative to the United Nations and former Foreign Minister of Brazil This edited volume examines the policies and practices of rising powers on peacebuilding. It analyzes how and why their approaches differ from those of traditional donors and multilateral institutions. The policies of the rising powers towards peacebuilding may significantly influence how the UN and others undertake peacebuilding in the future. This book is an invaluable resource for practitioners, policy makers, researchers and students who want tounderstand how peacebuilding is likely to evolve over the next decades.